Dolphinfish Bycatch in Spanish Mediterranean Large Pelagic Longline Fisheries, 2000–2010 - David Macías; José C. Báez; Salvador García-Barcelona; José M. Ortiz de Urbina (The Scientific World Journal)
The aim of this paper is to describe the dolphinfish bycatch rates in the longline fisheries of the Western Mediterranean and modelling the nominal bycatch abundance and distribution of dolphinfish from the Spanish Mediterranean as a function of technical, geographical, and seasonality factors. Our results indicate that the impact of the pelagic and semipelagic longline on the dolphinfish population is relatively low (1.083 fishes per 1000 hooks), in contrast with the greater effect on the target species population. We obtained a statistically significant logistic model, with the following factors: technical characteristics of the fishery, geographical location, and seasonality. Drifting surface longliners targeting albacore is the gear with the highest effect on Mediterranean dolphinfish population. The technical characteristics of the fishery and seasonality factors have an important role in explaining the absence or presence of dolphinfish bycatch in the different boat strata, gear types, and seasons. Moreover, sea surface temperature and lunar phases also present additional explanations. Lunar phase as SST has been frequently used as an explanatory variable affecting catch rates of dolphinfish.